A study on the semantic and lexicogrammatical features of the short story Mr. Know All by W. Somerset Maugham: A systemic functional analysis - Nguyễn, Thị Bích Liên (2016)
Chapter 1. General introductionpresents rationalefor the study, aim of the study, scope of the study, method of the study and design of the study. Chapter 2: Theoretical backgrounds–provides the theoretical framework of the study. Its focus is on introducing important concepts of systemic functional linguistics relevant to the topic of the study and a brief introduction to theauthor and the story Mr. Know All. Chapter 3:Data analysis–analyses the semantic and lexicogrammatical features of the story Mr. Know Allto seehow transitivity, mood & modality, and theme arepatterned in the story and provides commentsbased on these findings. Chapter 4 -Conclusion –summarizes what has been studied; provides some implications for teaching and learning English; and makes somesuggestions for further research.